الذكر في الطرق الصوفية بين السنة والبدعة - Azlina Abdullah; عزلينا بنت عبد الله (Universiti Sains Islam Malaysia, 2022)
The main purpose of this research is to discussion in depth about the fiction of zikr in Sufis. However, it also explains the basic of Sophism's like the concept of tasauf, the develop meant of tasnuf and the sources of the school of Sufis. Sophism's zikr has many levels; most of the practices are beyond our knowledge sometimes it out understanding. This is the reasoning why the indulges in the subject. The research also touches on the advantages of zikr, the transformation of zikr that is considered bid'ah suyyiah. Because of this paper project, it can conclude that most of sufi's zih are taken from islamic sources. Only a little bit of zikr is has bid'ah sayyiah. For completing the task, take some learned Islamic scholars in Islamic University College of Malaysia (KUIM). Also did literature review in the library of KUIM and other university, and the Islamic center in Kuala Lumpur